(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This comprehensive article provides a detailed exploration of the United Kingdom’s multifaceted economic framework, encompassing its diverse industries, resilient manufacturing sector, and the spectrum of natural resources found within Great Britain. The narrative delves into the historical significance of the UK’s economic evolution, from its Industrial Revolution heritage to its present-day prowess in service-oriented industries.